2018
DOI: 10.1155/2018/9284639
|View full text |Cite
|
Sign up to set email alerts
|

Channel Characteristics of Rail Traffic Tunnel Scenarios Based on Ray‐Tracing Simulator

Abstract: The tunnel scenario is a major rail communication scenario. In this paper, the radio channel characteristics of tunnel scenarios with different carrier frequencies, different distances between the transmitter (Tx) and receiver (Rx), and cross sections are simulated with a ray-tracing tool. Key parameters such as path loss, Rician K-factor, root mean square (RMS) delay spread, and angular spread are studied. According to the results, higher frequencies introduce larger path loss and the presence of the vehicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In order to execute channel measurements in subway tunnels, some scholars use raytracing method to simulate channel propagation characteristics. In [8,9], based on measurement and simulation data, PL of straight tunnel and curved tunnel at 2.4 GHz were studied, respectively, and it was found that the radius of curvature of tunnel had a significant influence on channel characteristics. In curved tunnels, there was an additional loss of received power.…”
Section: Introductionmentioning
confidence: 99%
“…In order to execute channel measurements in subway tunnels, some scholars use raytracing method to simulate channel propagation characteristics. In [8,9], based on measurement and simulation data, PL of straight tunnel and curved tunnel at 2.4 GHz were studied, respectively, and it was found that the radius of curvature of tunnel had a significant influence on channel characteristics. In curved tunnels, there was an additional loss of received power.…”
Section: Introductionmentioning
confidence: 99%